(untitled) (Research, Society and Development, 2023)
Introduction: Postural control is maintained through synergistic interaction between somatosensory, visual, vestibular and neuromusculoskeletal systems. This interaction keeps the Center of Gravity (CG) within the Support Base (SB) and Stability Limit (SL), and provides quick responses when there are external disturbances. Postural control can be evaluated by posturography, using a computerized force platform to which the patient is submitted to tests that provide different sensory conditions, and promotes stimulation of the optokinetic oculomotor reflex, and is relevant for the diagnosis of parameters that induce instability, in various clinical conditions, which also includes the perception of dizziness by the patient and complaints of body imbalance. Objective: to bring the method of evaluation of Horus® computerized posturography in patients with dysfunctions in vestibular-based body balance. Method: The Horus® computerized force platform, is a system designed for the diagnosis of body balance in the upright position, consists of 15 different tests, with variation of visual stimulus, head position, body position and use foam pad for partial suppression of body balance. Evidence from 01 to 08 shows fixed acronym and description as a result of the requirements of sensory analysis, and tests 09 to 15 can be modified by the examiner. Conclusion: This is an important tool, because it allows us to have access to quantitative data on body balance assessment, and from these results we can direct physical therapy interventions in order to design strategies for motor coordination and postural control.